Willingness to Pay Rumah Tangga di Kota Padang terhadap Produk Ramah Lingkungan - Adita, Afifah Putri; Nazer, M.; Sari, Delfia Tanjung (SAFE-Network, 2023)
The growing number of people moving up to the consumptive class and the urbanization of rural communities to cities also increase the demand for products with plastic packaging which. The problem of plastic waste has become the government's priority in realizing the goal of sustainable development through circular economic practices. Encouraging the creation of environmentally friendly products in the industry has been done but the number of product innovations is still low. Another obstacle is that product sales are strongly linked to the general welfare of individuals and society. Therefore, exploring consumer desires towards environmentally friendly products becomes important because this new knowledge can be used by governments and manufacturers to promote environmentally friendly products in the long run consumption. This study attempts to investigate the WTP of households in Padang City against environmentally friendly products and found factors that affect the WTP value. Using the contingent valuation method (CVM), the findings showed that willingness to pay (WTP) for eco-friendly products was significantly associated with gender, education, household income and price of alternative products. The results also showed that the average household is willing to pay about Rp 34,472.- for one product. These micro-level investigations can be a useful framework in organizing information and strategies on how households value eco-friendly products.